INCREASED INCIDENTS OF STUNTING IN MAJENE DISTRICT WEST SULAWESI - Masriadi; Mahmud, Nur Ulmy; Javid, Nazli; Wulandari, Sri; Fachrin, Suharni A. (Universitas Airlangga, 2024)
Introduction: Stunting is a condition of chronic malnutrition caused by malnutrition that occurs over a long period of time, caused by food supply that does not match the nutritional needs of children. Developmental delay occurs when the child is still in the mother's womb and appears when the child is two years old. There is prevalence of stunted toddlers in 6 districts in West Sulawesi, namely Majene District (40.6%), Polewali Mandar District (39.3%), Mamasa (38.6%), Mamuju (33.8%), Central Mamuju (28.1%), and Install Wood (25.8%). Aims: Analysis of risk factors for stunting in Majene district. Method: This type of study is an observational study with a case-control study design. The number of toddlers is 418 toddlers. The sample for this study included 112 toddlers aged 0-59 months. The sampling technique is by means of proportional sampling. Results: the study shows that Kadarzi (OR 17.274), self-efficacy (OR 3.240), and socio-culture are risk factors for increased stunting in Majene District, KAP variable (OR 0.321) is a protective factor against stunting in Majene District. Conclusion: Kadarzi, self-efficacy, and socio-cultural variables are risk factors for stunting in Majene Regency. It is hoped that mothers will pay more attention to their toddler's nutritional intake from birth, especially on exclusive breastfeeding, MP-ASI, and various foods, and routinely bring their toddlers to the posyandu every month to find out their toddler's nutritional growth and development.